1982
DOI: 10.1254/jjp.32.1013
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin-induced anorexia in rats: A structure-activity study by intraventricular injections.

Abstract: Abstract-The anorectic potency of salmon, porcine and human calcitonins (sCT, pCT and hCT, respectively) and two sCT-fragments were compared in rats. Intraventricular injections of sCT (0.062 and 0.031 nmole/animal) significantly reduced the normal feeding and body weight. The effect appeared to be dose-dependent, reversible and lasted longer than 6 hr. No anorexia ensued, however, on injections of mammalian hormones though tested in relatively high doses (pCT: up to 3.7 nmole, hCT: 3.7 nmole). The C-terminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 10 publications
2
22
0
Order By: Relevance
“…The lowest dose of sCT which Freed et al (5) employed to decrease feeding of rats was 0.20 U (0.015 nmole) per animal. Later we confirmed that the minimum effective dose would be above 0.2 U per rat (6). Assuming the distribution volume as 2.0-0.2 ml, injection of 0.20 U would give 7.5 nM or higher as the final concentration which cor responds to the minimum effective concen tration estimated herein for the novel in vitro effect.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The lowest dose of sCT which Freed et al (5) employed to decrease feeding of rats was 0.20 U (0.015 nmole) per animal. Later we confirmed that the minimum effective dose would be above 0.2 U per rat (6). Assuming the distribution volume as 2.0-0.2 ml, injection of 0.20 U would give 7.5 nM or higher as the final concentration which cor responds to the minimum effective concen tration estimated herein for the novel in vitro effect.…”
Section: Discussionsupporting
confidence: 77%
“…Recently, we have compared the anorectic potency of the three calcitonins and the two sCT fragments used in this experiment (6 …”
Section: Discussionmentioning
confidence: 99%
“…Com parative studies (4,5) on the anorectic potency of calcitonins of various animal origins have provided the results supporting the classical concept established for the hypocalcemic activity that the hormone of fish origin is biologically far more potent than the mammalian congeners (6).…”
supporting
confidence: 54%
“…sCT (4500 U/mg) was the synthetic product and pCT (170 U/mg) the natural one from the Armour Pharmaceutical Co. (Kankakee, IL, U.S.A.). Intracerebroven tricular cannulation was done as described previously (4). The antinociceptive activity was evaluated by the method of Randall and Selitto (8).…”
mentioning
confidence: 99%
“…Moreover, aggregation stimulates undesirable immune responses, resulting in resistance or allergic reactions in patients (13,14), and drug-induced cytotoxicity (15). On the contrary, sCT shows a higher potency combined with a longer in vivo half-life when compared with hCT and a substantially lower propensity to aggregate (7,11), but it has been shown to develop side effects such as anorexia and vomiting (16,17). When aggregation is prevented by drastic chemical conditions, hCT shows a much higher potency than sCT (18); however, those conditions are difficult to implement during the production, storage, and administration to patients, explaining why hCT has never been extensively used as a therapeutic.…”
mentioning
confidence: 99%